2018
DOI: 10.1021/acs.analchem.8b02055
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Instrument-Free Bar-Chart SpinChip Integrated with Nanoparticle-Mediated Magnetic Aptasensors for Visual Quantitative Detection of Multiple Pathogens

Abstract: A portable multiplexed bar-chart SpinChip (MB-SpinChip) integrated with nanoparticle-mediated magnetic aptasensors was developed for visual quantitative instrument-free detection of multiple pathogens. This versatile multiplexed SpinChip combines aptamer-specific recognition and nanoparticle-catalyzed pressure amplification to achieve a sample-to-answer output for sensitive point-of-care testing (POCT). This is the first report of pathogen detection using a volumetric bar-chart chip, and it is also the first b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 73 publications
1
72
0
Order By: Relevance
“…Beside the POD‐like nanozyme tags, Wei et al. () established a pressure‐based SpinChip for pathogen detection using the aptamer‐modified CAT‐like Pt NPs as a signal tag. All the above studies demonstrate the wide flexibility of nanozyme tags in a variety of detection methods.…”
Section: Principles Of Detection Using Enzyme‐mimetic Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the POD‐like nanozyme tags, Wei et al. () established a pressure‐based SpinChip for pathogen detection using the aptamer‐modified CAT‐like Pt NPs as a signal tag. All the above studies demonstrate the wide flexibility of nanozyme tags in a variety of detection methods.…”
Section: Principles Of Detection Using Enzyme‐mimetic Nanomaterialsmentioning
confidence: 99%
“…In addition to common recognition elements, Liu, Han et al (2018) used POD-like MnO 2 NS conjugated with a specific nonapeptidefusion protein pVIII as a sandwich immunoassay tag for Vibrio parahaemolyticus (V. parahaemolyticus) detection. Beside the PODlike nanozyme tags, Wei et al (2018) established a pressure-based SpinChip for pathogen detection using the aptamer-modified CAT-like Pt NPs as a signal tag. All the above studies demonstrate the wide flexibility of nanozyme tags in a variety of detection methods.…”
Section: Nanozyme As a Signal Tagmentioning
confidence: 99%
“…With great advantages of tunability in activities, high stability as well as easy storage, noble-metal nanozymes show great potential in biosensing. [48][49][50][51][52][53][54][55][56][57][58][59][60] Numerous noble metal nanomaterials such as AuNPs, [48][49][50][51] Pt NPs, [52,53] PdPt, [54] PtAu, [55,56] PdCu, [57] FeCu NPs, [58] Pd@Pt NPs [59] and Au@Pt core/shell nanorods, [46,60] etc. have been widely studied for the detection of microbial pathogens.…”
Section: Detection Of Pathogenic Microorganisms By Nanozymes 21 Nobmentioning
confidence: 99%
“…[52,53] For instance, Yang's group [52] reported that PtNPs generated more than 400 times more O 2 per second than common catalase, resulting in much higher detection sensitivity. Recently, Wei and co-workers [53] prepared a multiplexed bar-chart SpinChip integrated with PtNP-mediated aptasensors for visual quantitative detection of three major foodborne pathogens, that is, Salmonella enterica, E. coli, and Listeria monocytogenes. As illustrated in Figure 2, the nanoparticle-mediated aptasensor was assembled by DNA hybridization between magnetic capture-beads-DNA and aptamer-DNA-PtNPs.…”
Section: Mono-metal-based Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation